2020
DOI: 10.31729/jnma.4792
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Shade and Skin Colour: A Descriptive Cross-Sectional Study

Abstract: Introduction: Selection of proper tooth shade is one of the most significant factors influencing patients’ aesthetic perception and improved prosthesis acceptance. Guidelines in the dental literature suggest age, sex, colour of skin, hair and eye for selecting tooth shade when past records cannot be obtained. The objective of the study was to observe the most common tooth shade in relation to the skin colour and the prevalence of the same in relation to age and sex. Methods: A descriptive cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Some previous studies that investigated the relationship between tooth color and skin color used conventional shade matching with a makeup skin color chart/shades [ 1 , 7 , 17 ], or Fitzpatrick skin type test [ 18 ], and a conventional tooth color selection using tooth shade tabs. These studies concentrated on and described color according to the relationship between the lightness (value) of the tooth with the lightness (value) of the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies that investigated the relationship between tooth color and skin color used conventional shade matching with a makeup skin color chart/shades [ 1 , 7 , 17 ], or Fitzpatrick skin type test [ 18 ], and a conventional tooth color selection using tooth shade tabs. These studies concentrated on and described color according to the relationship between the lightness (value) of the tooth with the lightness (value) of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving an aesthetically pleasing smile is among the difficulties dentists must overcome. Harmonizing the surrounding facial structures, such as hair, complexion, and eyes, as well as age, with the color of the teeth was seen as a difficult problem [ 1 , 2 ]. Choosing tooth color is subjective with no set processes or protocols to follow.…”
Section: Introductionmentioning
confidence: 99%
“…However, other factors such as gender and skin complexion should also be associated with tooth shade to provide a more lifelike prosthesis for the replacement of anterior and posterior teeth. [ 20 21 ] Furthermore, the various other shade guides affect the determination of tooth shade. [ 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Jahangiri et al concluded that 50% of persons with low-value teeth had fair skin, whereas 17% had dark skin [6]. However, a study in Nepal [13], and another in India [14], exhibited no difference between all skin colors and tooth shades. Another study conducted in Korea reported that lighter and less chromatic central incisors were characteristics of female subjects in all age groups [15].…”
Section: Introductionmentioning
confidence: 99%